Analysis of Factors Influencing Patients to Choose a Hospital for Inpatient at Al Fuadi Binjai General Hospital - Ginting, Inayanti Khairiyah; Nuraini, Nuraini; Nasution, Ramadhani Syafitri (PROMOTOR, 2024)
Inpatient services at Al-Fuadi Binjai Hospital aim to provide the best care for patients, but the services provided sometimes cause complaints and dissatisfaction of patients who choose to be hospitalized at the hospital. The patient's decision to choose to be treated at Al Fuadi Binjai Hospital is based on Kotler's decision-making theory and Andersen's health care search theory. The purpose of this study was to analyze the factors that influence patients to choose a hospital for hospitalization. Types of research This is an analytical survey research by design cross sectional. Research conducted at Al Fuadi Binjai General Hospital. The study population was 319 people, and the sample was obtained 178 people. The data used are primary and secondary data. Data analysis in univariate, bivariate using chi-square and multivariate using multiple logistic regression at a 95% confidence level (a=0.05). The results showed that the influencing factors The decision to choose hospitalization at Al Fuadi Binjai General Hospital was culture (values in the family) (p = 0.037), confidence (0.031), quality of health worker services (0.023), motivation (p = 0.008), facilities (p = 0.002), and speed of service (p = 0.000), while the perception variable had no effect (p = 0.206). The dominant variable influencing patients' decision to choose hospitalization at Al Fuadi Binjai General Hospital is the speed of service. Patients who stated that service at Al Fuadi Binjai General Hospital was fast, were 5.2 times more likely to choose readmission than patients who stated that service at Al Fuadi Binjai General Hospital was slow. Fast service is the main reason patients choose hospitalization because it has an impact on the speed of patient recovery. It was concluded that the patient's decision to choose hospitalization at Al Fuadi Binjai General Hospital was influenced by the culture, beliefs, quality of service of health workers, motivation, facilities and speed of service. It is recommended for patients to provide input through the suggestion box on complaints felt during treatment to improve the quality of service so that patients without hesitation decide to re-hospitalize when patients and families are sick.